The Influence of Organizational Culture and Work Discipline on Employee Performance at PT. Jasamarga Tollroad Operator Jakarta - Cikampek Branch - Selvyana, Ajeng Amelda; Nurlenawati, Netti; Anggela, Flora Patricia (Journal of Social Research, 2023)
With the entry of the Industrial Revolution 4.0, PT. Jasamarga Tollroad Jakarta-Cikampek Branch Operator must be swift to face all challenges and uncertain changes in business direction. To manage and strengthen the viability of a company, businesses must continue to evolve and innovate in the human resources function. The purpose of this study is to identify and evaluate how organizational culture and work discipline impact employee productivity at PT Jasamarga Tollroad Operator Jakarta-Cikampek Branch. This study used quantitative, descriptive, and verification methodologies. Cluster random sampling is used as a sampling method in these investigations. 478 employees make up the population, while 120 responses make up the sample. Multiple linear regression analysis with SPSS is the method used in processing this research data. Overall work discipline, company culture, and employee performance all fall into the "good" category, according to the findings. The findings of the analysis show that the factors that influence work discipline and organizational culture both positively and significantly affect employee performance. Employee performance is simultaneously positively and significantly influenced by organizational culture and work discipline.